2019
DOI: 10.3390/ijms20133236
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Enhance Multiple Myeloma Metastatic Dissemination

Abstract: Extracellular vesicles (EVs) represent a heterogeneous group of membranous structures shed by all kinds of cell types, which are released into the surrounding microenvironment or spread to distant sites through the circulation. Therefore, EVs are key mediators of the communication between tumor cells and the surrounding microenvironment or the distant premetastatic niche due to their ability to transport lipids, transcription factors, mRNAs, non-coding regulatory RNAs, and proteins. Multiple myeloma (MM) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 102 publications
0
42
0
Order By: Relevance
“…Lipids are also an integral part of EVs, and several studies have described EV lipid composition. EVs are rich in cholesterol, phospholipid (phosphatidylserine, phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol), sphingomyelin, glycosphingolipids, diglyceride, polyglycerol, and ganglioside GM3 [88][89][90]. Specific lipids are enriched in EVs compared with their parent cells.…”
Section: Ev-associatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids are also an integral part of EVs, and several studies have described EV lipid composition. EVs are rich in cholesterol, phospholipid (phosphatidylserine, phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol), sphingomyelin, glycosphingolipids, diglyceride, polyglycerol, and ganglioside GM3 [88][89][90]. Specific lipids are enriched in EVs compared with their parent cells.…”
Section: Ev-associatedmentioning
confidence: 99%
“…Studies have shown a [90]. As part of vesicle membranes, EV lipids provide the structural rigidity and stability required during the budding process as well as the ability to protect EV cargo, promoting autocrine or paracrine signaling [89,94]. EV uptake can also be affected by lipid composition, with lipid rafts allowing the EVs to fuse into recipient cells [89].…”
Section: Ev-associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, extracellular PVT1 and especially circPVT1 may have a putative role in hematological malignancies. In MM, extracellular vesicles have a supportive role during metastatization by promoting angiogenesis, uptake at distant premetastatic niches and activation of osteolytic activity [129]. Given their known role in angiogenesis, as proved in solid tumors, and their ability to shape cellular function, as demonstrated in immune cells, we can hypothesize that PVT1 and circPVT1 may be loaded as RNA cargo in extracellular vesicles released by plasma cells, in order to instruct the tumor microenvironment (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Nanosized exosomes (70-150 nm) are the most prominent members of these so-called extracellular vesicles (EVs) and are released from body fluids such as urine, ascites, and plasma 73,74 . Moreover, they are liberated over all kinds of body cells (epithelium cells, haematopoietic cells, adipocytes, healthy and malignant cells) 75 , released in almost all cell types under physiological and pathophysiological conditions and mediate intercellular contacts 76 . A theranostic solution could be represented by the nanosized EVs, which may transmit biomarkers of diseases and/or vectors of therapeutic molecules, offering a unique opportunity to use a combination of different markers specifically expressed for tumour-derived EVs 74,76,77 .…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%